The closure property of H $\mathcal{H}$ -tensors under the Hadamard product - Lixin Zhou; Jianzhou Liu; Li Zhu (Journal of Inequalities and Applications, 2017)
Abstract In this paper, we investigate the closure property of H $\mathcal {H}$ -tensors under the Hadamard product. It is shown that the Hadamard products of Hadamard powers of strong H $\mathcal{H}$ -tensors are still strong H $\mathcal{H}$ -tensors. We then bound the minimal real eigenvalues of the comparison tensors of the Hadamard products involving strong H $\mathcal{H}$ -tensors. Finally, we show how to attain the bounds by characterizing these H $\mathcal{H}$ -tensors.